Arterial pulse waves measured with EMFi and PPG sensors and comparison of the pulse waveform spectral and decomposition analysis in healthy subjects - Matti Huotari; Antti Vehkaoja; Kari Määttä; Juha Röning (Finnish Social and Health Informatics Association, 2013)
The purpose of this study is to show the time domain and frequency domain analysis of signals recorded with Electromechanical Film (EMFi) and Photoplethysmographic (PPG) sensors in arterial elasticity estimation via pulse wave decomposition and spectral components obtained from left forefinger, wrist, and second toe arteries. ECG and pulse waves from the subjects were recorded from 7 persons (30‐60 y) in supine position. Decomposition of the pulse waves produces five components: percussion, tidal, dicrotic, repercussion, and retidal waves. Pulse wave decomposition parameters between EMFi and PPG are compared to detect variables for information on person's arterial elasticity. Results show that elasticity information in the form of pulse wave decomposition from PPG and EMFi waves is obtainable and shows clear shortening between percussion wave and tidal wave peak time in PPG waveforms with age. The spectral information obtained with frequency domain analysis could also be valuable in assessment of the arterial elasticity. In addition, both PPG and EMFi measurements are absolutely non‐invasive and safe. In PPG measurement, the sensors are on the opposite sides of the finger tip, however, EMFi measurement needs the good skilled operator attaching the sensor on the patient's wrist by touching gently to obtain accurate waveforms.